2020
DOI: 10.1037/xlm0000835
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms of prediction updating that impact the processing of upcoming word: An event-related potential study on sentence comprehension.

Abstract: One of the most compelling pieces of evidence for the presence of predictions in language comprehension comes from event-related potential (ERP) studies which show that encountering an adjective whose gender marking is inconsistent with that of a highly expectable noun leads to an effect at the adjective. Until now the mechanism underlying this effect has been unknown. The present study tests a novel hypothesis whereby the effect at adjectives reflects prediction updating, which in turn impacts the N400 genera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 68 publications
(126 reference statements)
4
28
1
Order By: Relevance
“…Yielding further support for prediction revision, we observed that N400 amplitude gradually decreased with the revised predictability of D.S. Fleur, et al Cognition 204 (2020) 104335 the noun after the gender-mismatching article (see also Szewczyk & Wodniecka, 2020). Importantly, our analysis controlled for other relevant influences on N400 amplitude (word length and frequency, word position, semantic similarity to the predicted noun, and plausibility).…”
Section: Revising a Noun Predictionsupporting
confidence: 65%
See 3 more Smart Citations
“…Yielding further support for prediction revision, we observed that N400 amplitude gradually decreased with the revised predictability of D.S. Fleur, et al Cognition 204 (2020) 104335 the noun after the gender-mismatching article (see also Szewczyk & Wodniecka, 2020). Importantly, our analysis controlled for other relevant influences on N400 amplitude (word length and frequency, word position, semantic similarity to the predicted noun, and plausibility).…”
Section: Revising a Noun Predictionsupporting
confidence: 65%
“…3 This hypothesis, originally coined as a potential explanation of pre-nominal prediction effects reported by Van Berkum et al (2005), is similar in spirit to recent 'prediction updating' proposals about the functional significance of the N400 component (Rabovsky, 2020;Szewczyk & Wodniecka, 2020). However, these proposals take N400 amplitude to index change in a semantic featurebased probabilistic representation of sentence meaning, and do not assume prediction of word form.…”
Section: Two Open Questionsmentioning
confidence: 81%
See 2 more Smart Citations
“…It does raise the question, however, whether listeners reliably or consistently use adjectival inflection information to inform their noun predictions. When a misprediction is evident, people may use the available gender information to revise their initial noun prediction, and perhaps even change their initial prediction to a new noun (as demonstrated by concomitant effects on noun-elicited N400s, e.g., Fleur et al, 2020;Szewczyk & Wodniecka, 2020). However, when evidence for misprediction is less compelling or ambiguous, people might be 'reluctant' to let go of their initial noun prediction (e.g., Nieuwland et al, 2018).…”
Section: Implications For Predictive Processingmentioning
confidence: 99%